Analysis on the Control of Natural Fracture Network on Reservoir Seepage Characteristics in Ordos Basin - Wang, Zhenze; Wang, Xinyue (International Journal of Computer Science and Information Technology, 2025)
Natural fracture network not only greatly changes the permeability and fluid distribution of reservoir, but also affects the flow velocity of fluid. According to the causes of cracks, they can be divided into two types: regional cracks and structural cracks. The former is related to the overall structure and sedimentary process of the basin, while the latter is due to local stress concentration caused by crustal movement. The existence of these fractures makes the reservoir show significant heterogeneity, especially the connectivity and directionality of the fractures, which has a key impact on the plane permeability ratio of the reservoir. In addition, the fracture opening has a direct impact on reservoir permeability and plane permeability ratio, and controls the distribution and flow path of fluid in the reservoir. It is pointed out that when the direction of natural fracture is parallel to the direction of maximum horizontal principal stress, the permeability efficiency of fluid can be effectively improved. The formation of complex fracture network further improves the permeability and production of reservoir and provides a better flow channel for the effective development of oil and gas resources. Therefore, it is very important to understand and predict the characteristics of natural fracture network for optimizing oil and gas field development strategy. This study reveals the important control effect of natural fracture network on reservoir seepage characteristics, which provides theoretical support and technical guidance for improving the development efficiency and reducing the development cost of oil and gas resources in Ordos Basin.